Temperature-responsive methacrylamide polyampholytes. Issue 49 (15th June 2017) - Weaver, Lucy G.; Stockmann, Regine; Thang, San H.; Postma, Almar
Abstract : The effective modulation of polymer cloud points in water is demonstrated through a series of charged, temperature-responsive methacrylamide-based polyampholytes. Abstract : A series of methacrylamide-based polyampholytes were synthesised for the first time and their temperature responsive properties investigated. N -[3-(Dimethylamino)propyl]methacrylamide (DMAPMAm) and methacrylic acid (MAA) were copolymerised in equimolar amounts along with N -( tert -butyl)methacrylamide (tBMAm) via RAFT polymerisation, forming a series of polymers with varying tBMAm content. A variety of solvents were assessed to determine the optimal conditions for synthesis. The solution properties of the resultant polymers were then determined via turbidimetry and NMR. Results from this study show that tBMAm was an effective modulator of T CP events when it was present in levels of 16% or more of the total monomers in the polymer chain. Below this threshold, polymers displayed properties akin to traditional polyampholytes due to the antipolyelectrolyte effect. Above this level however, the polymers displayed properties analogous to other temperature-responsive polymer systems. Interestingly changes in both pH and addition of salt led to an increase in the polymer cloud points, and in some cases loss of thermoresponsivity entirely, despite the high level of anionic and cationic charges present in the side chains.